Clinical Outcomes of Drug-Eluting versus Bare-Metal In-Stent Restenosis after the Treatment of Drug-Eluting Stent or Drug-Eluting Balloon: A Systematic Review and Meta-Analysis - Yi-Xing Yang; Yin Liu; Chang-Ping Li; Peng-Ju Lu; Jiao Wang; Jing Gao (Journal of Interventional Cardiology)
Background. Although drug-eluting stents (DES) have reduced the rates of in-stent restenosis (ISR) compared with bare-metal stents (BMS), DES related ISR (DES-ISR) still occurs and outcomes of DES-ISR remain unclear. The objective of this meta-analysis was to investigate the long-term clinical outcomes of patients with DES-ISR compared with patients with BMS related ISR (BMS-ISR) after the treatment of DES or drug-eluting balloon (DEB). Methods and results. We searched the literature in the main electronic databases including PUBMED, EMBASE, Cochrane Library, and Web of Science. The primary endpoints were target lesion revascularization (TLR) and target vessel revascularization (TVR). The secondary endpoints included all cause death (ACD), cardiac death (CD), myocardial infarction (MI), stent thrombosis or re-in-stent restenosis (ST/RE-ISR), and major adverse cardiovascular events (MACEs). A total of 19 studies with 6256 participants were finally included in this meta-analysis. Results showed that the rates of TLR (P<0.00001), TVR (P<0.00001), CD (P=0.02), ST/RE-ISR (P<0.00001), and MACEs (P<0.00001) were significantly higher in the DES-ISR group than in the BMS-ISR group. No significant differences were found between the two groups in the rates of MI (P=0.05) and ACD (P=0.21). Conclusions. Our study demonstrated that patients with DES-ISR had worse clinical outcomes at the long-term follow-up than patients with BMS-ISR after the treatment of DES or DEB, suggesting that DES and DEB may be more effective for BMS-ISR than that for DES-ISR. Positive prevention of DES-ISR is indispensable and further studies concentrating on detecting the predictors of outcomes of DES-ISR are required.